Prevalence of pre-existing dysglycaemia among inpatients with acute coronary syndrome and associations with outcomes. (August 2019) - Mahendran, Dinesh C.; Hamilton, Garry; Weiss, Jeremy; Churilov, Leonid; Lew, Jeremy; Khoo, Kaylyn; Lam, Que; Robbins, Raymond; Hart, Graeme K.; Johnson, Douglas; Hare, David L.; Farouque, Omar; et al.
Highlights: Three quarters of patients aged 54 or more, admitted with acute coronary syndrome had dysglycaemia. Pre-diabetes accounted for almost half the dysglycaemic patients. Inpatients with diabetes had higher odds of acute pulmonary oedema. Inpatients with diabetes had higher odds of acute coronary syndrome recurrence. Abstract: Aims: We aimed to confirm the hypothesis that dysglycaemia including in the pre-diabetes range affects a majority of patients admitted with acute coronary syndrome (ACS) and is associated with worse outcomes. Methods: In this prospective observational cohort study, consecutive inpatients aged ≥ 54 years with ACS were uniformly tested and categorised into diabetes (prior diagnosis/ HbA1c ≥ 6.5%, ≥48 mmol/mol), pre-diabetes (HbA1c 5.7–6.4%, 39–47 mmol/mol) and no diabetes (HbA1c ≤ 5.6%, ≤38 mmol/mol) groups. Results: Over two years, 847 consecutive inpatients presented with ACS. 313 (37%) inpatients had diabetes, 312 (37%) had pre-diabetes and 222 (25%) had no diabetes. Diabetes, compared with no diabetes, was associated with higher odds of acute pulmonary oedema (APO, odds ratio, OR 2.60, p < 0.01), longer length of stay (LOS, incidence rate ratio, IRR 1.18, p = 0.02) and, 12-month ACS recurrence (OR 1.86, p = 0.046) after adjustment, while no significant associations were identified for pre-diabetes. Analysed as a continuous variable, every 1% (11 mmol/mol) increase in HbA1c was associated with increased odds of APO (OR 1.28, P = 0.002) and a longer LOS (IRR 1.05, P = 0.03). Conclusions: The high prevalence of dysglycaemia and association with poorer clinical outcomes justifies routine HbA1c testing to identify individuals who may benefit from cardioprotective anti-hyperglycaemic agents and, lifestyle modification to prevent progression of pre-diabetes.